1985
DOI: 10.1111/j.1365-2621.1985.tb10476.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Rosemary Oleoresin in Turkey Sausage

Abstract: Rosemary oleoresin (20 ppm) was used as an antioxidant in turkey breakfast sausages prepared with 75% hand deboned turkey meat and 25% mechanically deboned turkey meat. It was compared to similarly formulated products with butylated hydroxyanisole/butylated hydroxytoluene (BHAIBHT, 200 ppm) and a control with no antioxidants. 2-Thiobarbituric acid-reactive substances in samples stored at 4°C demonstrated that rosemary oleoresin was comparable to a commercial blend of BHA/BHT/citric acid in suppressing lipid au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
11

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(67 citation statements)
references
References 25 publications
4
51
1
11
Order By: Relevance
“…Moreover, untreated samples reached the highest value corresponding to smell (score 3) and 10-20 % of discoloration (score 3), as early as 21 days. These results were in agreement with those obtained by Barbut et al (1985) who found that Ros inhibited undesirable odor appearance in Turkey sausage stored at 4 °C. Also, these results were in harmony with those recorded by Escalante et al (2001) who showed that Ros alone or with AA, extended the fresh beef patty odo during storage time.…”
Section: Chemical Analysissupporting
confidence: 83%
“…Moreover, untreated samples reached the highest value corresponding to smell (score 3) and 10-20 % of discoloration (score 3), as early as 21 days. These results were in agreement with those obtained by Barbut et al (1985) who found that Ros inhibited undesirable odor appearance in Turkey sausage stored at 4 °C. Also, these results were in harmony with those recorded by Escalante et al (2001) who showed that Ros alone or with AA, extended the fresh beef patty odo during storage time.…”
Section: Chemical Analysissupporting
confidence: 83%
“…During freeze storage of mechanically deboned turkey meat, extensive autooxidation occurs resulting in a decreased functionality of the meat (Mielnik et al 2003). However, the storage life of mechanically deboned meat can be extended with antioxidants (Barbut et al 1985). The most important process in the oxidation of lipids in meat is the peroxidation of polyunsaturated fatty acids from cell membranes (Keller & Kinsella 1973).…”
mentioning
confidence: 99%
“…Results concerning carnosine were in agreement with the report of Decker and Crum (1991), who found that 1.5% carnosine inhibited rancid odor formation in frozen salted ground pork as determined by sensory panel. Barbut et al (1985) reported that rosemary preserved aroma quality and delayed odor related to oxidative rancidity. This delay was of similar magnitude to a mixture of BHA/BHT in raw and fried turkey sausages.…”
Section: Sensory Analysismentioning
confidence: 99%
“…At day 20, values were significantly lower (p 5 0.05) in patties not subject to UV radiation; percentages of inhibition with respect to the control were 74, 71 and 59% for darkness, low-UV lamp and standard light, respectively. The antioxidant activity of rosemary is very well known; it has been proved to be very effective as antioxidant in fresh, frozen or cooked meats (Barbut, Josephson, & Maurer, 1985;Djenane et al, 2002;Murphy, Kerry, Buckley, & Gray, 1998;Sa´nchez-Escalante et al, 2001). Formanek et al (2001) reported that rosemary extracts showed similar antioxidative activities to BHA/BHT mixtures in patties stored under aerobic packaging conditions or modified atmospheres with elevated oxygen levels, during refrigerated storage or illuminated retail display at 4 8C for eight days.…”
Section: Lipid Oxidationmentioning
confidence: 99%